Antimicrobial Activity of Nauclea Latifolia Smith on Multiresistant Bacterial Strains - Ngassaki, Raoul; Ampa, Raoul; Gouollaly, Tsiba; Moyen, Rachel; Ahombo, Gabriel (International Journal of Innovative Research in Medical Science, 2022)
Nauclea latifolia Smith (Rubiaceae) is a plant with medicinal properties much better known in sub-Saharan Africa in the traditional pharmacopoeia for its numerous pharmacological activities. It is a very abundant tree or shrub in West and Central Africa. Its wide use in traditional medicine has prompted us to carry out an in vitro evaluation of its antimicrobial potential on multidrug-resistant strains in order to ensure consistency between the prescriptions and the potential activities of the chemical constituents present. N. latifolia Sm. due to the presence of numerous chemical families has interesting biological activities. The aqueous and hydroalcoholic extracts from the bark and roots of the plant have proven antimicrobial activity. These extracts inhibit the proliferation of multidrug resistant strains of S. aureus, E. coli and K. pneumoniae. On the other hand, these extracts showed no efficacy on the strains of C. albicans at the doses used (200 mg/ml; 100 mg/ml and 50 mg/ml).